Virtualization From the Desktop to the Enterprise - Wolf, Chris; Halter, Erick M. (Apress : Imprint: Apress, 2005)
Creating a virtual network allows you to maximize the use of your servers. Virtualization: From the Desktop to the Enterprise is the first book of its kind to demonstrate how to manage all aspects of virtualization across an enterprise. (Other books focus only on singular aspects of virtualization, without delving into the interrelationships of the technologies.) This book promises to cover all aspects of virtualization, including virtual machines, virtual file systems, virtual storage solutions, and clustering, enabling you to understand which technologies are right for your particular environment. Furthermore, the book covers both Microsoft and Linux environments.